Beyond presidentialism and parliamentarism democratic design and the separation of powers - Ganghof, Steffen 1971- (Oxford University Press, 2021)
This text elaborates a theory of 'semi-parliamentary government', an often neglected form of government that instantiates the principle of the separation of powers, by demonstrating how it reconciles important benefits of both presidential and parliamentary systems
Keywords: Demokratie; Gewaltenteilung